Clay Mineral Identification for the Utilization of the Brick Industry in Samarinda using X-Ray Diffraction (XRD) Analysis - Raharjanti, Ni'matul Azizah; Ismunandar, Wisnu; Sutan, Syamsidar; Andhika, Muhammad Wira; Priatama, Muhammad Haykal Bayu (Universitas Negeri Gorontalo, 2024)
The clay minerals occurrences can be utilized into various products, including bricks. Brick industry often used the materials taken from the local area. The objective of the research is to identify the lithology of the brick material as well as the mineral consist in the soil or material, including clay mineral. The analysis is carried out in field observation and X-Ray Diffraction (XRD) analysis. The analysis resulting the lithology of the research area is predominantly sandstone and the bricks material is taken from the clayey soil part of from the quartz sandstone lithology. The quartz sandstone predominantly composed by quartz (97%) and plagioclase as minor mineral (3%). The analysis of the clay soil sample in quartz sandstone layer which used as the main component of the brick showing that the minerals composition are mainly quartz (95%) and plagioclase as minor mineral (3%), while the clay mineral that detected is kaolinite (2%). The formation of the kaolinite is interpreted as the result of the weathering of plagioclase trough hydrolysis process. From those data, it is identified that the brick in the research area mainly composed by quartz and clay mineral as kaolinite is formed in just minor abundance.